Seldin and Giebisch's the kidney : physiology & pathophysiology. - Alpern, Robert J.; Herbert, Steven C.; Seldin, Donald W., 1920-2018; Giebisch, Gerhard H. (Elsevier Academic Press, 2008)
A classic nephrology reference for over 20 years, Seldin & Giebischs The Kidney, is the acknowledged authority on renal physiology and pathophysiology. The fourth edition follows the changed focus of nephrology research to the study of how individual molecules work together to affect cellular and organ function, emphasizing the mechanisms of disease. With over 40 new chapters and over 1000 illustrations, this edition offers the most in-depth discussion anywhere of the physiologic and pathophysiologic processes of renal disease. Comprehensive, authoritative coverage progresses from molecular biology and cell physiology to clinical issues regarding renal function and dysfunction. If you research the development of normal renal function or the mechanisms underlying renal disease, Seldin & Giebischs The Kidney is your number one source for information. Offers the most comprehensive coverage of fluid and electrolyte regulation and dysregulation in 51 completely revised chapters unlike Brenner & Rector's The Kidney which devotes only 7 chapters to this topic. Includes 3 sections, 31 chapters, devoted to regulation and disorders of acid-base homeostasis, and epithelial and nonepithelial transport regulation. Brenner & Rector's only devotes 5 chapters to these topics. Previous three editions edited by Donald Seldin and Gerhard Giebisch, world renowned names in nephrology. The title for the fourth edition has been changed to reflect their considerable work on previous editions and they have also written the forward for this edition. Over 20 million adults over age 20 have chronic kidney disease with the number of people diagnosed doubling each decade making it America's ninth leading cause of death.